The classroom as a laboratory for historical thinking: a pedagogical approach to analyzing past and society - Parada-Ulloa, Marcos; Burgos-Videla, Carmen (Frontiers in Education, 2025)
This study addresses the teaching of Social Sciences and History from a critical perspective, proposing the classroom as a laboratory for socio-historical analysis. Traditional education reproduces dominant narratives that reinforce social inequalities, exclude subaltern voices, and limit the development of critical thinking among students. The objective is to analyze how the classroom can become a space for resistance and critical reflection by incorporating historical thinking and critical pedagogy to foster the active construction of knowledge. A documentary methodology with a bibliographic design and critical-reflective approach was used. Through content analysis, relevant texts were selected and coded from various academic databases, prioritizing theoretical coherence with the study’s objective. Four key dimensions were identified: the reproduction of educational inequalities, critical thinking as a form of resistance, the transformation of historical narratives, and the teaching of history as a social practice. Additionally, a differentiated application of the approach by educational level (primary, secondary, and higher) was proposed, emphasizing the benefits of the historical method and interdisciplinarity in developing critical thinking. Theoretical evidence suggests that the classroom can be re-signified as a transformative space if inclusive, collaborative, and historically contextualized methodologies are promoted. Structural and institutional barriers must be overcome through critical educational policies and specific teacher training. Historical education, when critical and interdisciplinary, contributes to forming committed citizens capable of analyzing and transforming social reality from an ethical and emancipatory perspective.